The Influence of the Project-Based Learning Model on Student Learning Outcomes and Creativity in the Excretory System Material in High School - Rahmadani, Anisa Putri; Agustina, Lina (Universitas Muhammadiyah Prof. Dr. Hamka, 2025)
Background: In the 21 st century, education is highly needed as something important to compete in the current global era with several skill components that students must possess, namely the 4Cs (critical thinking, communication, collaboration, creativity, and innovation). This research aims to investigate the implementation of the project-based learning (PjBL) model on student learning outcomes and creativity in the excretory system material in 11th-grade Senior High School. Methods: The type of this research is experimental research using a one group posttest only design. The sample for this research is class XI-3 with 32 students and class XI-4 with 31 students. The sampling was conducted using the population sampling technique or the sampling of the entire population. During the research, the data analysis technique used was descriptive statistical analysis. Results: The findings obtained from the research conducted indicate that the application of the project-based learning (PjBL) model on student creativity falls into the very creative category with an average score of 89.00, and for learning outcomes, it shows a significant difference with an average score of 76.09 obtained from the control class, while the experimental class obtained an average score of 90.32. Conclusions: The project-based learning (PjBL) model influences students learning outcomes and creativity because it can provide guidance for students to discover learning concepts, help students solve problems, and apply knowledge from everyday life as learning so that students can develop their abilities and the learning conducted is not monotonous.